Investigating the size-dependent toxicological effects of zinc oxide nanoparticles on Caenorhabditis elegans and the inhibitory potential of Cytochrome P450 isozymes - Chowdhury, Lamia Noushin Sadeque (2024)
Zinc oxide nanoparticles (ZnONPs) are used in several industries including the cosmetics, textiles, and therapeutics. Wild-type Caenorhabditis elegans (N2) is commonly used as an ecotoxicological model, and as an in vivo model to understand the toxicity of xenobiotics in humans. Cytochrome P540 (CYP) isozymes are responsible for drug metabolism in humans, and its inhibition may lead to adverse drug reactions due to the decreased metabolism and subsequent delayed clearance of co-administered drugs. However, the size-dependent toxicological potential of ZnO particles towards N2 and inhibitory potential towards CYP isozymes are not well known. Firstly, this project aimed to investigate the size-dependent toxicological potential of ZnONP50 (zinc oxide nanoparticles <50 nm), ZnONP100 (zinc oxide nanoparticles <100 nm), and ZnOBP (zinc oxide bulk particle) towards the reproductive capacity, pharyngeal pumping rate, and lifespan of N2. Additionally, gene expression studies were carried to out to assess the variation of the nematode’s cep-1 and pmk-1 genes. Secondly, this project aimed to elucidate the size-dependent in vitro inhibitory effect and mode of inhibition of the ZnO particles towards CYP1A2, CYP2A6, CYP2B6, CYP2C8, CYP2E1, CYP2J2, and CYP3A5.